Measurement of the first harmonic modulation in the right ascension distribution of cosmic rays detected at the Pierre Auger Observatory: towards the detection of dipolar anisotropies over a wide energy range - Sidelnik, Iván Pedro; Aab, A.; Allekotte, Ingomar; Almela, Daniel Alejandro; Bertou, Xavier Pierre Louis; Dova, Maria Teresa; Figueira, Juan Manuel; Filevich, Alberto; Garcia, Beatriz Elena; Gomez Berisso, Mariano; Gómez Vitale, P. F.; González, N.; et al. (Sociedade Brasileira de Fisica, 2013)
Fil: Sidelnik, Iván Pedro. Centro Atomico Bariloche and Instituto Balseiro; Argentina